2023
DOI: 10.3390/antiox12071476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tannic Acid Supplementation on the Intestinal Health, Immunity, and Antioxidant Function of Broilers Challenged with Necrotic Enteritis

Abstract: Clostridium perfringens causes necrotic enteritis (NE) after proliferation in the intestine of poultry, resulting in considerable losses to the poultry industry. This study aimed to investigate the impact of tannic acid on the antioxidant, immunity, and gut health of broilers with NE. In the experiment, 630 one-day-old Cobb500 male chicks were randomly divided into six treatment groups, with seven replicate cages and with fifteen birds in each cage. The treatment groups were as follows: control group (NC), cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that flavonoids stimulate bone defect regeneration, minimize inflammation, and have a significant anticatabolic effect by reducing trabecular bone loss and increasing bone mineral density [44]. Research conducted on Cobb 500 chicks with necrotic enteritis showed that dietary supplementation of TA (250, 500, 750, and 1000 mg/kg) resulted in decreased TNFα levels and increased levels of anti-inflammatory parameters (T-AOC, IL-4, and IL-10) in serum [11]. Similarly, favorable effects were observed in studies on rats with induced inflammation that were given TA at doses of 25 or 50 mg/kg [45].…”
Section: Anti-inflammatory Activity Of Tannic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that flavonoids stimulate bone defect regeneration, minimize inflammation, and have a significant anticatabolic effect by reducing trabecular bone loss and increasing bone mineral density [44]. Research conducted on Cobb 500 chicks with necrotic enteritis showed that dietary supplementation of TA (250, 500, 750, and 1000 mg/kg) resulted in decreased TNFα levels and increased levels of anti-inflammatory parameters (T-AOC, IL-4, and IL-10) in serum [11]. Similarly, favorable effects were observed in studies on rats with induced inflammation that were given TA at doses of 25 or 50 mg/kg [45].…”
Section: Anti-inflammatory Activity Of Tannic Acidmentioning
confidence: 99%
“…Microbiological analysis of the cecum in Cobb 500 broilers with necrotic enteritis showed that TA administration improved gut barrier function and regulated gut flora. Moreover, the decreased levels of D-lactic acid and diamine oxidase in the serum indicate the potential positive effect of TA in maintaining gut barrier integrity [11].…”
Section: The Relationship Between Tannic Acid the Gut Microbiota And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary TA can also alleviate tissue inflammation and protect intestinal health by lowering the mRNA levels of tissue inflammation elements and increasing the mRNA levels of intestinal intact proteins in broilers [ 11 , 12 , 13 ]. It has been shown that TA can alleviate the inflammation of broilers with NE conditions and enhance the antioxidative ability by activating the Nrf2-Keap1 signaling pathway in rats [ 14 , 15 , 16 , 17 ]. However, whether TA could improve antioxidant capacity and alleviate oxidative stress through the Nrf2-Keap1 signaling pathway in broilers with NE condition has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%